How does radiotherapy affect the adhesion of universal adhesive to enamel and dentin? a qualitative and quantitative analysis? = Efecto de la radioterapia a la adhesión del adhesivo universal al esmalte y dentina? un análisis cualitativo y cuantitativo? - Oglakci, Burcu
This study investigated the shear bond strength (SBS) of a universal adhesive to enamel/dentin; 1) that had undergone radiotherapy (RT) and 2) that were readily restored and had undergone RT. Enamel and dentin surfaces were obtained from 90 intact human molars. They were randomly divided into six groups according to the presence and timing of irradiation (RT0:no radiotherapy/control, RT1:RT before restoration, RT2:RT after restoration groups) and adhesive application modes (etch&rinse/ER, self-etch/SE)(n=15). A universal adhesive and resin composites were applied. The radiotherapy protocol was conducted with 60 Gy. The SBS test was subjected (1mm/min) and failure type analysis was performed. The resin-enamel/dentin interfaces were examined. Data were statistically analyzed. For enamel and dentin, the presence and timing of irradiation did not significantly influence the SBS values (p>0.05). For enamel, significantly higher SBS values were obtained using etch&rinse mode than self-etch mode (p<0.05). The predominant failure was mixed type. Loss of enamel prisms and obliterated irregular dentinal tubules were found for the radiotherapy-treated specimens. Resin tags were clearer in the irradiated enamel treated with ER than SE. Irradiation with different timings did not influence the bond strength to enamel and dentin, negatively. Irrespective of radiotherapy, the etch&rinse mode caused higher bond strength to enamel than self-etch mode.